Study on Modification Technology and Meshing Performance of Locomotive Traction Gear - Shi Xiaochun; Zhang Riming; He Weidong (Jixie chuandong)
Considering the factors such as the deformation of the box body,the bearing and the shaft and the assembling clearance,the finite element method is used to analyze the contact state and load distribution of the traction gear. According to partial load in the meshing process,the optimum gear profile modification curve is optimized by using genetic algorithm. Through the comparison and analysis of the two meshing states of the forward and reversal of the locomotive gear,it can be found the load distribution on the teeth is more uniform,the stress concentration phenomenon caused by partial load is improved,and the maximum value of contact stress and bending stress significantly is reduced. The result shows the modification curve has a good effect.